Hurdle Rates and Project Development Efforts - Dutta, Sunil; Fan, Qintao (The Accounting Review, 2009)
ABSTRACT: We examine the optimal choice of hurdle rates in a capital budgeting setting in which a manager receives superior information regarding the profitability of an investment project. Unlike the prior capital budgeting literature that treats the distribution of investment returns as exogenous, we consider a scenario in which the manager can engage in upfront project development activities to improve the quality of investment opportunity. To motivate the project development effort while ensuring truthful information flow, the optimal hurdle rate is always lower than what it would be if the manager's project development effort were directly observable. We show that the optimal hurdle rate can even be below the firm's cost of capital under plausible circumstances. We also examine how the optimal hurdle rate varies with the ex ante quality of the firm's investment opportunities, and find that optimal hurdle rates will be higher in firms whose investment opportunities are relatively good or relatively poor than in firms with investment opportunities of intermediate quality.